Constructing divisia monetary aggregates for Nigeria - Yakubu. A. Bello; Salihu Audu; Hamman Ibrahim; Ali. I. Gambo; Farida. B. Usman; Solomon O. A. Ejila; Ejiro J. Ubiakwoyibo; Chukwuma K. Okeke; Jennifer A. Kalu (CBN Journal of Applied Statistics, 2022)
This study computes Divisia monetary aggregates DM1, DM2, and DM3 for Nige- ria using the Tornqvist-Theil quantity index for the period 2007M12 to 2020M12 and evaluates the performance of the higher-order aggregate (DM3) with a corre- sponding higher aggregate of the simple sum broad money supply (M3). Applying the indicators to money demand function the results showed that DM3 performed better than the matching simple sum measure M3 due to its faster convergence rate. This is because the Divisia aggregates contain additional information in the form of user-costs and spending shares that are not considered in the compilation of the traditional measure, information that may be important for the proper execution of monetary policy. It is therefore, recommended that the Divisia broad money index be used as complement to the simple sum broad money supply for policy decisions.
Keywords: C32; E41; E51; 330; Cointegration; demand for money; Divisia monetary aggregate